Emerging Powers and Global Governance : Whither the IMF? - Mohan, Rakesh (IMF Working Papers; Working Paper, 2015)
The governance structure in global bodies like the IMF continues to be disproportionally dominated by advanced economies. Sustained rapid growth in emerging and developing economies (EDEs) in the past 2-3 decades has led to their growing relative weight in the global economy, but with little increase in their voice in the IMF. The emergence of regional financial arrangements reflects the growing dissatisfaction of the EDEs with the current framework. The global economy is on the cusp of an epochal change moving the fulcrum of economic power from the North Atlantic towards Asia after more than 200 years. This must be recognized and responded to adequately.